Managing uncertainty in logistics service supply chain. (1st December 2006) - Choy, K.L.; Li, Chung-Lun; So, Stuart C.K.; Lau, Henry; Kwok, S.K.; Leung, Dennis
Many third party logistics (3PL) providers in South China are small and medium-sized companies and lack of systematic mean on handling information. Uncertainties are created in the business processes due to insufficient information for decision-making. In this study, a logistics information system called Integrated Logistics Information Management System (ILIMS) is proposed. It aims to manage the information flow efficiently between the involved parties in the logistics supply chain through integrating business processes and increasing information transparency to reduce uncertainty. In addition, it provides an effective channel for the 3PL providers to communicate with different contracted suppliers as well as customers through wireless Internet applications. A case study of applying ILIMS in a local 3PL company is discussed. By using this generic system, supply chain uncertainty that associates with the logistics processes can be reduced and leads to a significant performance improvement in the overall order fulfilment process.